2021
DOI: 10.1007/s00277-021-04644-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of COVID-19 in haematological malignancies: experience from tertiary care centre in India

Abstract: There is limited evidence on various clinical aspects of SARS-CoV-2 infection in patients with haematological cancers. The risk factors, prognosis, and outcome of patients with haematological cancers with coexistent COVID-19 need to be explored in different subsets of population. A single-institutional prospective observational study was conducted at a tertiary level medical institute in North India. The clinical details of the recruited patients having haematological malignancies and diagnosed with COVID-19 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In a multivariate cox regression, the following types of HM were shown to bear the greatest risk for death from COVID-19: acute myeloid leukemia (3.49, 1.56–7.81), multiple myeloma (2.48, 1.31–4.69), and non-Hodgkin’s lymphoma (2.19, 1.07–4.48). Data reported in other studies [6, 14-16, 19] were similar. Interestingly, while age, HM severity, and shorter time from HM diagnosis were strongly associated with increased mortality, other comorbidities and time interval between last HM treatment and COVID-19 infection were not [6].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In a multivariate cox regression, the following types of HM were shown to bear the greatest risk for death from COVID-19: acute myeloid leukemia (3.49, 1.56–7.81), multiple myeloma (2.48, 1.31–4.69), and non-Hodgkin’s lymphoma (2.19, 1.07–4.48). Data reported in other studies [6, 14-16, 19] were similar. Interestingly, while age, HM severity, and shorter time from HM diagnosis were strongly associated with increased mortality, other comorbidities and time interval between last HM treatment and COVID-19 infection were not [6].…”
Section: Resultssupporting
confidence: 85%
“…These differences were even more pronounced when looking only at patients with newly diagnosed (<1 year) HM (HR 6.18 [4.31–8.86] than the general population and 2.24 [1.34–3.76] than patients with SM). The increased risk of patients with HM to have severe COVID-19 at presentation, to have a longer duration of hospital admission, and be more likely to die is consistent in reported studies across the globe when compared to all patients [14-16], patients with SM [13, 17], and patients treated with immunosuppressive medications [18]. In a large survey performed by the Scientific Working Group Infection in Hematology of the European Hematology Association, including 3,801 HM patients with COVID-19, 64% of patients developed severe or critical disease, 18% were admitted to an intensive care unit, and 31% died [6].…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Besides the French study reporting a mortality rate of 21% [ 7 ], one small study of thirteen patients (of which eight were hospitalized) reported a mortality rate of 23% [ 32 ]. One study on hospitalized haematological patients with severe COVID-19 reported a mortality rate of 54%, where all were given dexamethasone and remdesivir, and 45% also received CCP [ 33 ].…”
Section: Discussionmentioning
confidence: 99%